Thirteen years of oxcarbazepine exposures reported to US poison centers: 2000 to 2012. (October 2016) - Spiller, HA; Strauch, J; Essing-Spiller, SJ; Burns, G
Objectives: Oxcarbazepine (OXC) is a 10-keto analogue of carbamazepine used in patients with partial and secondary generalized seizures. We evaluated ingestions of OXC reported to US poison centers for adverse effects from supratherapeutic doses and/or overdose. Method: Retrospective analysis of data reported to National Poison Data System from single-substance OXC ingestions between January 2000 and December 2012. Results: There were 18, 867cases with a mean of 1451 exposures/year. The patients were predominantly adults with 5464 exposures in children <6 years (29%). The most commonly reported clinical effects were drowsiness ( n = 4703, 25%), vomiting ( n = 1559, 8%), tachycardia ( n = 590, 3%), agitated ( n = 342, 1.8%), hypotension ( n = 178, 0.9%), electrolyte disturbance ( n = 153, 0.8%), coma (n = 156, 0.8%), and seizures ( n = 121, 0.6%). There were 176 patients with a major effect of which 31 involved were children and 1728 (9%) patients with moderate effects of which 300 involved were children. Five deaths were reported in adults. Intentional exposure (e.g. suicide) was the reason for exposure in 68% of patients with major effects and in all fatalities. Fifty-three percent of adults and 38% of children were managed in a health-care facility (HCF). HCF utilization levels remained consistent. Discussion: Severe outcomes appear to be infrequent (<1%). Unlike other anticonvulsants OXC does not appear to be proconvulsant in overdose. Conclusion: Serious outcomes for OXC overdoses are unlikely in the pediatric patient. With only mild symptoms likely, observation at home may be appropriate for the majority of cases. In the adult population there appears to be few neurologic and cardiovascular complications even in the intentional exposure.